The International Baccalaureate External Examination Model - Torres-Skoumal, Marlene (R&E-SOURCE, 2014)
Curriculum-based external exit examinations systems are world wide the norm rather than the exception. Proponents of this system argue that imposing a curriculum-based external examination system improves student achievement and university success. Recent international multivariable statistical studies have shown a significant difference in student school exit and subsequent success among nations who employ this system. The main reason for this success is that well-designed external exit examinations induce improvements in instructional practices. This keynote will address the traits and achievements of the IB system with the hope that it can aid in the discussion and design of Austria’s external mathematics Matura.